(3TQM OjhGf CHj aQGS GdMeOGfis - (3CHi YHO Gddg GdMSjfj Hf CMeO Hf NGdhjg GdgePGfis; (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3bGd YHO Gddg GdMSjfi Hf NGdhjg ef Md ef GdTQa GdSGei GdMSH GdfGei eMd GdCejQ CHj aQGS TgOJ dg ThGgO GdYbd heGRGd jdbi Edi Ohf GdfGS TYQg hjNWQg hjNWQ Ydi fTQg s
(3BNQgG (B:s
(3bO YOe GdOfjG hdPGJgG hdcfg eGYOe GdUHQG Je TYQCHh aQGS hCNHGQg HMeO Gddg s
(3CHh aQGS gh GdCejQ GdMGQK Hf SYjO Hf MeOGf GdJZdHi GdeJhai (B357 (3hGdOjhGf QhGjg Hf NGdhjg hdjS ajg TQM EdG PcQ CjGeg hCNHGQg hefGSHGJgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs